2013
DOI: 10.11564/27-2-436
|View full text |Cite
|
Sign up to set email alerts
|

Trend and correlates of contraceptive use in rural and urban Ethiopia: is there a link to the health extension programme?

Abstract: When international funders shifted funding priorities from family planning to HIV/AIDS in the mid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
4
7
0
Order By: Relevance
“…Better wealth status is a protective factor against IPV [ 32 ] and a basis for women's sexual empowerment: ability to ask their partners to use condoms. Similar findings have been reported elsewhere, where wealth index increased the likelihood of MCU [ 23 , 33 , 34 ]. In addition, household wealth index, enhances access to modern contraceptives because women are able to afford purchase of modern contraceptive services.…”
Section: Discussionsupporting
confidence: 91%
“…Better wealth status is a protective factor against IPV [ 32 ] and a basis for women's sexual empowerment: ability to ask their partners to use condoms. Similar findings have been reported elsewhere, where wealth index increased the likelihood of MCU [ 23 , 33 , 34 ]. In addition, household wealth index, enhances access to modern contraceptives because women are able to afford purchase of modern contraceptive services.…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of married women who were current contraceptive method users was higher in households that had graduated as a model-family than in households that had not yet graduated as a model-family 16. Another assessment in Ethiopia also indicated that the increase in contraceptive use was largely attributable to the HEP 1719. Findings of studies on other community-based health programs in other countries also support this study.…”
Section: Discussionsupporting
confidence: 75%
“…It is a better way to engage men and to get information across to illiterate women. Adequate and regular information on family planning can erode the cultural mindsets on the attitudes towards acceptability of family planning choices particularly in the rural areas (Adebowale, et., 2013;Gurmu and Mturi, 2013;Khan, et al, 2008;Westoff and German, 1995). As part of the outcome of the multivariate analysis provided in our study, recent visit to health facility with or without family planning issues discussed reduces the probability of unmet need among those who visited.…”
Section: Discussionmentioning
confidence: 99%